Chinese moving image arts, 2015–2017: Observations and reflections. Issue 2 (4th May 2019) - Dong, Bingfeng; Feng, Junyuan; Jiang, Zoe Meng
Abstract: Since 2000, moving image art (yingxiang yishu) has gradually become a common term in the field of Chinese contemporary art. "Moving image art" remains an unstable category instructive of the tension and paradox between different forms and content in discursive practices. Mapping key conferences, publications, institutions and exhibitions, this article examines how the idea of "moving image art" arose, circulated, and acquired legitimacy in different Chinese-speaking areas. Rather than conjuring up moving image arts as yet another autonomous subject of art history, this article understands moving image art as a phenomenon resulted from complex processes of negotiation between the local, the trans-regional and the global, as well as conscious social, technological and cultural realities. From 2015 to 2017, there has been a surge of historical survey exhibition on moving image art in major museums in mainland China, Hong Kong and Taiwan, albeit with very different agendas. Rather than providing a linear story of the development of moving image arts, this article takes as its departure point important conferences, exhibitions, institutions that appeared from 2015 to 2017, with the aim to unravel complementing and sometimes competing historiographic attempts.